2018
DOI: 10.1103/physreve.97.040102
|View full text |Cite
|
Sign up to set email alerts
|

Universality from disorder in the random-bond Blume-Capel model

Abstract: Using high-precision Monte Carlo simulations and finite-size scaling we study the effect of quenched disorder in the exchange couplings on the Blume-Capel model on the square lattice. The first-order transition for large crystal-field coupling is softened to become continuous, with a divergent correlation length. An analysis of the scaling of the correlation length as well as the susceptibility and specific heat reveals that it belongs to the universality class of the Ising model with additional logarithmic co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 93 publications
2
21
0
Order By: Relevance
“…Finally, it is worth noting that the finite-size scaling behavior of both [W ] L and R [W ] L is affected by strong transient effects with a crossover length-scale L * ≈ 32, where a turnaround in the behavior sets off. This is consistent with previous observations on the scaling behavior of the correlation length and other thermodynamic observables of the system for the same range of parameters [39]. Indeed, in Ref.…”
Section: Figsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, it is worth noting that the finite-size scaling behavior of both [W ] L and R [W ] L is affected by strong transient effects with a crossover length-scale L * ≈ 32, where a turnaround in the behavior sets off. This is consistent with previous observations on the scaling behavior of the correlation length and other thermodynamic observables of the system for the same range of parameters [39]. Indeed, in Ref.…”
Section: Figsupporting
confidence: 93%
“…Indeed, in Ref. [39] it has been explicitly shown that L ≈ 32 is the apparent size where the first-order characteristic signatures of the transition disappear. Of course, we expect that the value of L * depends on the disorder strength r as well as on the strength of the first-order transition and it would be interesting to investigate the shift of this crossover length-scale as a function of ∆ and r. However this is a task that goes beyond the scope of the present work.…”
Section: Figmentioning
confidence: 99%
“…Additionally, the Kondo Effect is important in certain metallic compounds with dilute concentrations of magnetic impurities that cross over from a weakly-coupled Fermi liquid phase to a local Fermi liquid phase upon reducing the temperature below some threshold 39 . Furthermore, examples of strong crossover phenomena have also been recently discovered in classical models of statistical mechanics such as the Blume-Capel model and the random-field Ising model 40,41 .…”
mentioning
confidence: 98%
“…For an extensive discussion on the Blume-Capel model, including the phase diagram and its critical properties we refer the reader to Ref. [12][13][14][15].…”
Section: Model and Simulation Detailsmentioning
confidence: 99%